2017
DOI: 10.1038/srep44947
|View full text |Cite
|
Sign up to set email alerts
|

The epidemic dynamics of hepatitis C virus subtypes 4a and 4d in Saudi Arabia

Abstract: The relatedness between viral variants sampled at different locations through time can provide information pertinent to public health that cannot readily be obtained through standard surveillance methods. Here, we use virus genetic data to identify the transmission dynamics that drive the hepatitis C virus subtypes 4a (HCV4a) and 4d (HCV4d) epidemics in Saudi Arabia. We use a comprehensive dataset of newly generated and publicly available sequence data to infer the HCV4a and HCV4d evolutionary histories in a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 58 publications
(106 reference statements)
0
24
0
Order By: Relevance
“…In his recent study on the epidemic dynamics of HCV Al-Qahtani has demonstrated clearly that genotype 4 was transmitted between countries in the region but originated from Egypt. Viral spread between Saudi Arabia and Egypt is predominantly directed towards Saudi Arabia, showing that both HCV genotype 4 epidemics are connected through a source-sink relation, perhaps linked to the large flow of Egyptian migrant workers [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In his recent study on the epidemic dynamics of HCV Al-Qahtani has demonstrated clearly that genotype 4 was transmitted between countries in the region but originated from Egypt. Viral spread between Saudi Arabia and Egypt is predominantly directed towards Saudi Arabia, showing that both HCV genotype 4 epidemics are connected through a source-sink relation, perhaps linked to the large flow of Egyptian migrant workers [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The different trait diffusion models come with different assumptions and their application may also depend on the spatial resolution of the location data. The discrete model makes abstractions of precise geographic data-sometimes made necessary by the absence of fine-scale geographic information-but may still provide a powerful approach to infer epidemiological dynamics, as illustrated in applications like investigating the relevance of migration on public health planning [13][14][15][16][17], identifying the determinants of the spread of dog rabies virus in North Africa [18], or determining the role of swine movements in the dynamics of influenza in the United States [19]. More specifically to HIV, phylogeographic analyses have been used to reconstruct the early continental expansion of HIV-1 group M in Africa [20] and the spread of subtype B across the globe [21] and to North America [22].…”
Section: Introductionmentioning
confidence: 99%
“…As the chronic nature of most HCV infections hampers reliably reconstructing contact networks from patient interviews, virus genetic data can be a valuable alternative source of information for elucidating the geographic history of virus lineages (e.g. 5,6). Using such data, we have recently shown that for the most prevalent subtype among PWID in Spain (40%, 7 ), HCV1a, infections often link to infections abroad -in recent years >50% link to Western European countries, mostly European Union (EU) member states -as opposed to other infections within Spain.…”
Section: To the Editormentioning
confidence: 99%